Fluorine-containing polyimide/polysilsesquioxane carbon molecular sieve membranes and techno-economic evaluation thereof for C3H6/C3H8 separation - Shin, Ju Ho; Yu, Hyun Jung; Park, Junhyung; Lee, Albert S.; Hwang, Seung Sang; Kim, Seok-Jhin; Park, Sunghwan; Cho, Kie Yong; Won, Wangyun; Lee, Jong Suk (ELSEVIER, 2020)
Herein, we investigated the effect of thermo-oxidative crosslinking of siloxanes on the C3H6/C3H8 separation performance of carbon molecular sieve (CMS) membranes derived from polymer blends of a fluorine-containing polyimide and a ladder-structured polysilsesquioxane (PI/LPSQ). The PI/LPSQ precursors self-generated fluorinated gases, which possibly lead to the cleavage of double-stranded siloxanes during pyrolysis. At the same time, residual siloxanes underwent thermo-oxidative crosslinking, which resulted in densification into nonporous inorganic SiO2 phases. Such impermeable SiO2 phases adversely affected the gas diffusion, decreasing C3H6 permeability but contributed to the significant enhancement in the C3H6/C3H8 selectivity up to as much as 67, because of the substantially enhanced diffusivity selectivity. Density functional theory-based pore size distribution analysis exhibited that the narrower pores in the range of 5.0-5.5 angstrom emerged for the PI/LPSQ (80/20 w/w) CMS, supporting the enhancement in C3H6/C3H8 selectivity. Also, PI/LPSQ (80/20 w/w) CMS fibers aged for 30 days showed C3H6 permeance of 2.9 GPU and a C3H6/C3H8 selectivity of 57. Furthermore, the technoeconomic analysis verified the economic feasibility of the proposed membrane for the C3H6/C3H8 separation process. It reflected that higher C3H6 permeability plays a significant role in reducing the total cost of C3H6/C3H8 separation process as long as the C3H6/C3H8 selectivity is above 30, implying the significance of anti-aging in CMS hollow fiber membranes.
Keywords: HOLLOW-FIBER MEMBRANES; GAS SEPARATION; ETHYLENE/ETHANE SEPARATION; SILICA MEMBRANES; POLYIMIDE; PERFORMANCE; PYROLYSIS; FABRICATION; PLASTICIZATION; POLYMER